School counsellor's roles in minimising adolescents' attrition from schools - Aluede, Oyaziwo (Orientación y Sociedad.)
Counselling ways (rendering financial advice, providing encouragement, reassurances and support), which the school counselllors could adopt to help the school system minimize the increasing incidence of school dropout, were advanced.